Two smiling marchers with banner - Sahl, Ted (photographer):::Creator::::::::::::
Photograph show two smiling marchers carrying a banner that reads, "March on Washington, October 14, 1979". Other marchers follow the banner bearers during the National March on Washington for Lesbian and Gay Rights.